Website characteristics and web users' satisfaction in a higher learning institution. (2017) - Lee, Kian Guan; Chong, Chin Wei; Ramayah, T.
This paper aims to identify the characteristics of higher learning institution websites that will affect student satisfaction in Malaysian context. It develops one research model concerned with the determinants of higher learning institution website towards student satisfaction based on end-user computing instrument (EUCI) model. It was found that web presence, visual design and navigation design in higher learning institution website play a major role in creating satisfaction when using the website. This study contributes to academia as it tries to fulfil the gap in the area of higher learning institution website characteristics which is rather limited and unexplored in previous literature. The findings of this study can shed a light to higher learning website designer on factors or characteristics to focus on when designing the website. This research proves that findings on e-commerce website are also applicable in higher learning institution websites.